Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Wajib Pajak dalam Membayar Pajak Bumi dan Bangunan - Maria Fransisca Verenuela Tiba; Kenny Ardillah (UNIVERSITAS KALBIS, 2023)
This study aims to determine the effect of taxpayer awareness, tax sanctions, taxpayer income and level of trust. The number of samples used in this study were 100 respondents who were calculated based on the Slovin formula. The data was collected using a questionnaire method and processed using SPSS statistics. The results of this study indicate that taxpayer awareness and taxpayer income have a positive and significant effect, while tax sanctions and the level of trust have no and significant effect.